Response of Setaria italica to Different Management Practices Under Dryland Farming - Subramanian, P; Ganesaraja, V (Annals of Arid Zone, 2016)
An investigation on the response of dryland Setaria to intercropping, manuring and fertilizer levels revealed that growing Setaria wi* blackgram or field bean in 3:1 ratio in a replacement series with a basal application of 12.5 t FYM + 20 kg N + 10 kg P ha-1 gave 52.3% and 42% higher monetary returns and fodder to cattle population compared to the sole crop. The Land Use Equivalent was also greater by 11.2% in Setaria + blackgram combination and 4.9% in . Setaria + field bean combination over sole Setaria. Among the intercrops, blackgram is compara-tively less competitive and more of complimentary than field bean.